Social network contingency, symbolic management, and boundary stretching - Markõczy, L.; Li Sun, S.; Peng, Mike; Shi, W.; Ren, B. (John Wiley & Sons, 2013)
A firm's structural position within corporate networks may affect the extent to which it engages in boundary stretching practices. Since social norms support low CEO compensation, offering high CEO compensation in China can be seen as a boundary stretching practice. Setting up a compensation committee (CC) may be viewed as a form of symbolic management in China. We argue that firms operating within central corporate network positions opt to pay higher CEO compensation without engaging in symbolic management. On the other hand, firms operating in structural hole positions tend to either pay lower CEO compensation or use CCs as a symbolic management tool in order to pay higher CEO compensation. Our hypotheses are largely supported based on 7,618 firm-year observations in China. .